ChemInform Abstract: Nature‐Inspired Optimization of Hierarchical Porous Media for Catalytic and Separation Processes. Issue 27 (16th June 2016) - Trogadas, Panagiotis; Nigra, Michael M.; Coppens, Marc‐Olivier
Abstract: Review: 98 refs.